2014
DOI: 10.5152/balkanmedj.2014.13142
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Epidemiology and Aetiology of Acute Gastroenteritis in Adult Patients Presenting at the Infectious Diseases Hospital in Tirana, Albania

Abstract: Background: Acute gastroenteritis remains a common cause of hospital emergency room visits in Albania. However, the aetiology of severe gastroenteritis leading to hospitalization in adults frequently remains unclear. Aims: Our objective was to study the epidemiology and causes of community-acquired, acute gastroenteritis in adult patients presenting to hospital. Study Design: Cross sectional study. Methods: A prospective study was conducted from January 2010 to January 2012, among patients ≥15 years old with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…C. coli was identified in 12.3% patients and C. lari was not detected at all. This species distribution of Campylobacter is similar with that existing in our neighboring countries, as well as in many countries worldwide [7,9]. This variation might be attributed to demographic, geographic and study period differences between these studies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…C. coli was identified in 12.3% patients and C. lari was not detected at all. This species distribution of Campylobacter is similar with that existing in our neighboring countries, as well as in many countries worldwide [7,9]. This variation might be attributed to demographic, geographic and study period differences between these studies.…”
Section: Discussionsupporting
confidence: 85%
“…in the last two years of the study increased for more than 2 times in comparison with the isolation rate during the previous four years. With the isolation rate of 2.53 our results are comparable with the results revealed in the reports from some Balkan countries [7], but it is much lower than the isolation rates in many European countries [8]. Several factors such as consumer awareness, severity of a disease and its surveillance by the clinicians, affect the degree of isolation rate of Campylobacter as a food borne pathogen.…”
Section: Discussionsupporting
confidence: 83%
“…Viral diarrhea in developing countries is associated with hygienic habits of the population but also with consumption of food in restaurants and takeaways [4]. Only one fifth (11.8-22.4%) of our patients consumed food outside home immediately before the onset of symptoms.…”
Section: Discussionmentioning
confidence: 74%
“…The practical importance of differentiation between causes of viral gastroenteritis is often overlooked by general practitioners [3]. The reasons for this include primarily the treatment approach that is symptomatic in all cases of viral gastroenteritis, as well as the cost of diagnostic tests, which are still based on molecu-lar techniques and therefore usually unaffordable for patients in developing countries [4]. However, literature data indicate that there are differences in the incidence of individual causes of viral gastroenteritis, as well as in the severity of clinical symptoms, and it has been observed that these differences depend on geographic area, as well as socioeconomic status and hygienic habits of the study population [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that a significant correlation exists between stool bacterial multiplex PCR test results and the severe symptoms of acute diarrhea. Vomiting tended to be more frequent in the negative group (p = 0.08), per-haps because vomiting is common in diarrheal diseases of viral origin [23,24] and the multiplex PCR test used in this study did not include viral genera. The presence of WBCs in stool suggests an inflammatory process caused by bacterial spp., such as Salmonella spp., Shigella spp., C. jejuni, or C. difficile.…”
Section: Discussionmentioning
confidence: 92%